Hard alloy material and preparation method and application thereof

By using specific composition cemented carbide materials, including WC powder, TiB2 powder, Co powder, Ni powder, Mo powder, Cr3C2 powder and nanocomposite powder, the traditional cemented carbide materials are not tough and have poor durability during cutting. Problem, achieving higher wear resistance and service life.

CN119464874AInactive Publication Date: 2025-02-18SHENZHEN BOERDUN INNOVATION TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411624686.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing kitchen tools are not tough and not durable when cutting hard objects, resulting in deformation of the cutting edge and reducing service life. In addition, traditional cemented carbide materials are prone to adhesion, softening, material loss and other phenomena during high-speed cutting.

Method used

A cemented carbide material is adopted, and its raw materials include WC powder, TiB2 powder, Co powder, Ni powder, Mo powder, Cr3C2 powder and nanocomposite powder. Through specific raw materials composition and preparation methods, it forms high hardness and wear resistance. and fracture toughness materials.

Benefits of technology

It significantly improves the wear resistance and service life of cemented carbide, enhances room temperature bending strength and fracture toughness, and improves performance under high-speed cutting conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005134409900000071
    Figure BDA0005134409900000071
Patent Text Reader

Abstract

The invention belongs to the technical field of alloy materials, and particularly relates to a hard alloy material and a preparation method and application thereof. The hard alloy material comprises the following raw materials in percentage by mass: 70%-80% of WC powder, 5%-15% of TiB2 powder, 6%-9% of Co powder, 2%-8% of Ni powder, 0.4%-1.0% of Mo powder, 0.6%-1.6% of Cr3C2 powder and 3%-5% of nano composite powder. By adding the specific nano composite powder, the composite reinforced hard alloy die has higher hardness, good wear resistance and higher fracture toughness, and the service life of the composite reinforced hard alloy die is further prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy materials, and in particular relates to a cemented carbide material and a preparation method and application thereof. Background Art

[0002] Kitchen knives are a necessity in people's daily life, and they are needed for daily cooking. At present, kitchen knives generally have problems such as low toughness and durability when cutting hard objects, which causes the blade to deform and reduces its service life.

[0003] WC, as a refractory metal hard compound, is widely used in cemented carbide materials, especially in the field of tool manufacturing, where WC-based cemented carbide is the most typical and widely used type. Traditional WC-based cemented carbide refers to cemented carbide containing a binding phase such as Co. Traditional WC-based cemented carbide has high hardness, high strength and density, and has good toughness. It has important applications as a tool in the field of industrial processing and production. Because traditional cemented carbide tools contain a binding phase such as Co, when cutting at high speeds, especially when processing difficult-to-process materials such as titanium alloys, the cutting force is large and the cutting temperature is high. It is easy to cause adhesion, softening, material loss and other phenomena, which seriously affects the quality and precision of the processed materials, and also greatly reduces the service life of the tool.

[0004] In addition, the existing cemented carbide material manufacturing technology has the phenomenon of "the contradictory relationship between the high strength and high hardness of cemented carbide, and the contradictory relationship between high wear resistance and high toughness".

[0005] Chinese invention patent application CN108914018A discloses a hard alloy material for cutting tools, wherein the component ratio (mass fraction) of the hard alloy material for cutting tools includes 70-80 parts of iron, 1-1.5 parts of carbon, 10-15 parts of nickel, 2.5-8 parts of magnesium, 2-5 parts of aluminum, 3-6 parts of chromium, 1-1.5 parts of molybdenum, 2-3.5 parts of titanium, 1-2 parts of barium, 1-1.5 parts of vanadium, 10-15 parts of tungsten carbide, and 0.07-0.09 parts of rhenium. The final finished cutting tool of the hard alloy cutting tool obtained by the invention has poor wear resistance and substandard cutting quality in actual use, and its performance is not as good as that of the hard alloy made of WC as the matrix.

[0006] Based on this, the present invention provides a cemented carbide material and a preparation method thereof, which significantly improves the wear resistance and service life of the cemented carbide, and at the same time has higher room temperature bending strength and fracture toughness than traditional cemented carbide. Summary of the invention

[0007] In view of the deficiencies of the prior art, the present invention provides a cemented carbide material and a preparation method and application thereof, which further improves the strength, wear resistance, fracture toughness and service life of the alloy material.

[0008] In order to achieve the above-mentioned purpose of the present invention, the specific technical solution adopted by the present invention is:

[0009] A hard alloy material, wherein the raw materials of the hard alloy material include, by mass percentage, 70%-80% WC powder, 5%-15% TiB2 powder, 6%-9% Co powder, 2%-8% Ni powder, 0.4%-1.0% Mo powder, 0.6%-1.6% Cr3C2 powder and 3%-5% nano composite powder.

[0010] Among them, TiB2 powder can react with WC powder and Co powder in the solid phase in situ to generate ternary boride W2CoB2 hard phase, thereby improving the hardness of cemented carbide.

[0011] On the one hand, Mo powder can form a solid solution with the hard phase to improve the high temperature red hardness of cemented carbide; on the other hand, Mo powder can also exist in the bonding phase. The solid solution strengthening of Ni and Mo can significantly improve the toughness and high temperature oxidation resistance of the bonding phase in cemented carbide.

[0012] Preferably, the method for preparing the nanocomposite powder comprises the following steps:

[0013] (1) mixing graphene and anhydrous ethanol, and dispersing them by ultrasonication to obtain a mixture 1;

[0014] (2) mixing aluminum nitrate nonahydrate, yttrium nitrate hexahydrate, neodymium nitrate hexahydrate, sodium alginate and ethanol solution, adding the mixture to mixture 1, and sonicating to obtain mixture 2;

[0015] (3) heating the mixture 2, adjusting the pH, cooling and standing, centrifuging, washing, and drying to obtain a precursor powder;

[0016] (4) calcining the precursor powder to obtain nanocomposite powder.

[0017] Further preferably, the mass volume ratio of the graphene to anhydrous ethanol in step (1) is 10 mg: 15-25 mL; the mass ratio of the aluminum nitrate nonahydrate, yttrium nitrate hexahydrate, neodymium nitrate hexahydrate and sodium alginate in step (2) is 1: 0.8-1.2: 0.8-1.2: 0.1-0.2, the mass volume ratio of the aluminum nitrate nonahydrate to the ethanol solution is 1 g: 40-50 mL, and the mass concentration of the ethanol solution is 65%-75%.

[0018] Further preferably, the mass ratio of the graphene in step (1) to the aluminum nitrate nonahydrate in step (2) is 1:45-55, and in step (3), the mixture is heated to 75-80°C, the pH is adjusted to 7.5-8, the solution used to adjust the pH is an ammonia solution, and the mixture is allowed to stand for 22-26 hours, and the drying is vacuum drying.

[0019] Further preferably, the calcination procedure in step (4) is: heating to 1100-1150° C. at 3-5° C. / min and keeping the temperature for 60-80 min.

[0020] Preferably, the WC powder comprises, by mass percentage: 40%-60% of WC powder with a particle size of 0.6-0.8 μm and 40%-60% of WC powder with a particle size of 0.8-1.1 μm.

[0021] The present invention also relates to a method for preparing the above-mentioned cemented carbide material, comprising the following steps:

[0022] S1. Under nitrogen protection, the raw material of the cemented carbide material, the wet grinding medium and the forming agent are mixed and wet-grinded to obtain a slurry;

[0023] S2, vacuum drying the slurry, sieving, and obtaining alloy powder;

[0024] S3, pressing the alloy powder into a shape and performing vacuum sintering to obtain a cemented carbide material.

[0025] Preferably, the wet grinding medium in step S1 is anhydrous ethanol, the mass ratio of the wet grinding medium to the raw material of the cemented carbide material is 1:0.5-1, the molding agent is paraffin, and the addition amount of the paraffin is 2%-5% of the raw material of the cemented carbide material.

[0026] Preferably, in step S2, the steel is sieved with a mesh size of 100-200; in step S3, the sintering comprises low-temperature sintering, medium-temperature sintering and high-temperature sintering performed in sequence; the temperature of the low-temperature sintering is 440-480°C, and the holding time of the low-temperature sintering is 1-2h; the temperature of the medium-temperature sintering is 900-950°C, and the holding time of the medium-temperature sintering is 1-2h; the temperature of the high-temperature sintering is 1200-1500°C, and the holding time of the high-temperature sintering is 0.5-2h.

[0027] The present invention also relates to the use of the above-mentioned cemented carbide material or the cemented carbide material prepared by the above-mentioned preparation method in preparing kitchen knives.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The present invention not only has higher hardness, but also has good wear resistance and higher fracture toughness by adding specific nano-composite powder, thereby extending the service life of the composite reinforced cemented carbide mold;

[0030] (2) The present invention uses Co and Ni as the binding phase, so that W maintains a certain solid solution amount in Co and Ni, improves corrosion resistance and toughness, and further improves corrosion resistance by adding Cr3C2 to diffuse uniformly in the liquid phase;

[0031] (3) Titanium diboride is also added to the raw materials of the present invention, which has high hardness and anti-oxidation and corrosion resistance characteristics, and thus can effectively improve the hardness, high temperature oxidation resistance and corrosion resistance of cemented carbide;

[0032] (4) The neodymium oxide and yttrium oxide in the nanocomposite powder of the present invention can synergistically enhance toughness and refine grains; graphene helps to improve the hardness and wear resistance of the material; and aluminum oxide can not only form a lubricating film on the surface of the material to play a buffering role, but also further improve the wear resistance of the material. DETAILED DESCRIPTION

[0033] The present invention will be further described in detail below in conjunction with specific examples. The following examples are not intended to limit the present invention, but are only intended to illustrate the present invention. The experimental methods used in the following examples are generally conventional, unless otherwise specified, and the materials, reagents, etc. used in the following examples are commercially available, unless otherwise specified.

[0034] Example 1

[0035] A hard alloy material, wherein the raw materials of the hard alloy material are, by mass percentage, 73% WC powder, 10% TiB2 powder, 7% Co powder, 4% Ni powder, 0.8% Mo powder, 1.2% Cr3C2 powder and 4% nanocomposite powder;

[0036] The composition of the WC powder is: 60wt% of WC powder with a particle size of 0.6-0.8μm and 40wt% of WC powder with a particle size of 0.8-1.1μm.

[0037] Wherein, the preparation method of nano composite powder is:

[0038] (1) mixing graphene and anhydrous ethanol (the mass volume ratio of graphene to anhydrous ethanol is 10 mg:20 mL), and dispersing by ultrasonication to obtain a mixture 1;

[0039] (2) mixing aluminum nitrate nonahydrate, yttrium nitrate hexahydrate, neodymium nitrate hexahydrate, sodium alginate and 70 wt % ethanol solution, wherein the mass ratio of aluminum nitrate nonahydrate to graphene is 50:1, and the amount ratio of aluminum nitrate nonahydrate, yttrium nitrate hexahydrate, neodymium nitrate hexahydrate, sodium alginate and ethanol solution is 1:1:1:0.15:45 mL, and then adding the above mixture to mixture 1, ultrasonicating, to obtain mixture 2;

[0040] (3) heating the mixture from 2 to 75° C., adjusting the pH to 8 with an ammonia solution (a mixture of 25% ammonia water and anhydrous ethanol in a mass ratio of 1:4), cooling and standing for 24 h, centrifuging, washing with anhydrous ethanol 4 times, and vacuum drying at 105° C. to obtain a precursor powder;

[0041] (4) calcining the precursor powder, raising the temperature to 1100° C. at 4° C. / min, and keeping the temperature for 70 min to obtain a nanocomposite powder.

[0042] The preparation method of the above-mentioned cemented carbide material comprises the following steps:

[0043] S1. Under nitrogen protection, the raw material of the cemented carbide material, anhydrous ethanol and a paraffin molding agent are mixed and wet-ground (the amount of anhydrous ethanol added is 0.5 times the mass of the raw material of the cemented carbide material, and the amount of paraffin added is 2% of the mass of the raw material of the cemented carbide material) to obtain a slurry;

[0044] S2, vacuum drying the slurry, passing it through a 200-grit sieve to obtain alloy powder;

[0045] S3. The alloy powder is pressed into shape and subjected to low-temperature sintering, medium-temperature sintering and high-temperature sintering in sequence; the temperature of the low-temperature sintering is 460°C, and the holding time of the low-temperature sintering is 1.5 hours; the temperature of the medium-temperature sintering is 930°C, and the holding time of the medium-temperature sintering is 1.5 hours; the temperature of the high-temperature sintering is 1400°C, and the holding time of the high-temperature sintering is 1 hour, to obtain a cemented carbide material.

[0046] Example 2

[0047] A cemented carbide material, wherein the raw materials of the cemented carbide material are, by mass percentage, 70% WC powder, 13% TiB2 powder, 9% Co powder, 2% Ni powder, 1.0% Mo powder, 1.5% Cr3C2 powder and 4.5% nanocomposite powder;

[0048] The composition of the WC powder is: 55% of WC powder with a particle size of 0.6-0.8 μm and 45% of WC powder with a particle size of 0.8-1.1 μm.

[0049] Wherein, the preparation method of nano composite powder is:

[0050] (1) mixing graphene and anhydrous ethanol (the mass volume ratio of graphene to anhydrous ethanol is 10 mg:15 mL), and dispersing by ultrasonication to obtain a mixture 1;

[0051] (2) mixing aluminum nitrate nonahydrate, yttrium nitrate hexahydrate, neodymium nitrate hexahydrate, sodium alginate and 70 wt % ethanol solution, wherein the mass ratio of aluminum nitrate nonahydrate to graphene is 45:1, and the amount ratio of aluminum nitrate nonahydrate, yttrium nitrate hexahydrate, neodymium nitrate hexahydrate, sodium alginate and ethanol solution is 1:0.8:0.8:0.1:40 mL, and then adding the above mixture to mixture 1, ultrasonicating, to obtain mixture 2;

[0052] (3) heating the mixture from 2 to 75° C., adjusting the pH to 7.5 with an ammonia solution (mixed with 25% ammonia water and anhydrous ethanol in a mass ratio of 1:4), cooling and standing for 22 h, centrifuging, washing with anhydrous ethanol 4 times, and vacuum drying at 105° C. to obtain a precursor powder;

[0053] (4) calcining the precursor powder, raising the temperature to 1100° C. at 3° C. / min, and keeping the temperature for 60 min to obtain a nanocomposite powder.

[0054] The preparation method of the above-mentioned cemented carbide material comprises the following steps:

[0055] S1. Under nitrogen protection, the raw material of the cemented carbide material, anhydrous ethanol and a paraffin molding agent are mixed and wet-ground (the amount of anhydrous ethanol added is 0.5 times the mass of the raw material of the cemented carbide material, and the amount of paraffin added is 2% of the mass of the raw material of the cemented carbide material) to obtain a slurry;

[0056] S2, vacuum drying the slurry, passing it through a 100 sieve to obtain alloy powder;

[0057] S3. The alloy powder is pressed into shape and subjected to low-temperature sintering, medium-temperature sintering and high-temperature sintering in sequence; the temperature of the low-temperature sintering is 440°C, and the holding time of the low-temperature sintering is 2h; the temperature of the medium-temperature sintering is 900°C, and the holding time of the medium-temperature sintering is 2h; the temperature of the high-temperature sintering is 1200°C, and the holding time of the high-temperature sintering is 2h, to obtain a cemented carbide material.

[0058] Example 3

[0059] A cemented carbide material, wherein the raw materials of the cemented carbide material are, by mass percentage, 80% WC powder, 5% TiB2 powder, 6% Co powder, 4.5% Ni powder, 0.4% Mo powder, 0.6% Cr3C2 powder and 3.5% nanocomposite powder;

[0060] The composition of the WC powder is: 50% of WC powder with a particle size of 0.6-0.8 μm and 50% of WC powder with a particle size of 0.8-1.1 μm.

[0061] Wherein, the preparation method of nano composite powder is:

[0062] (1) mixing graphene and anhydrous ethanol (the mass volume ratio of graphene to anhydrous ethanol is 10 mg:25 mL), and dispersing by ultrasonication to obtain a mixture 1;

[0063] (2) mixing aluminum nitrate nonahydrate, yttrium nitrate hexahydrate, neodymium nitrate hexahydrate, sodium alginate and 70 wt % ethanol solution, wherein the mass ratio of aluminum nitrate nonahydrate to graphene is 55:1, and the amount ratio of aluminum nitrate nonahydrate, yttrium nitrate hexahydrate, neodymium nitrate hexahydrate, sodium alginate and ethanol solution is 1:1.2:1:0.2:50 mL, and then adding the above mixture to mixture 1, ultrasonicating, to obtain mixture 2;

[0064] (3) heating the mixture from 2 to 80° C., adjusting the pH to 8 with an ammonia solution (a mixture of 25% ammonia water and anhydrous ethanol in a mass ratio of 1:4), cooling and standing for 26 h, centrifuging, washing with anhydrous ethanol 4 times, and vacuum drying at 105° C. to obtain a precursor powder;

[0065] (4) calcining the precursor powder, raising the temperature to 1150°C at 5°C / min, and keeping the temperature for 80 min to obtain a nanocomposite powder.

[0066] The preparation method of the above-mentioned cemented carbide material comprises the following steps:

[0067] S1. Under nitrogen protection, the raw material of the cemented carbide material, anhydrous ethanol and a paraffin molding agent are mixed and wet-ground (the amount of anhydrous ethanol added is 0.5 times the mass of the raw material of the cemented carbide material, and the amount of paraffin added is 2% of the mass of the raw material of the cemented carbide material) to obtain a slurry;

[0068] S2, vacuum drying the slurry, passing it through a 200-grit sieve to obtain alloy powder;

[0069] S3. The alloy powder is pressed into shape and subjected to low-temperature sintering, medium-temperature sintering and high-temperature sintering in sequence; the temperature of the low-temperature sintering is 480°C, and the holding time of the low-temperature sintering is 1 hour; the temperature of the medium-temperature sintering is 950°C, and the holding time of the medium-temperature sintering is 1 hour; the temperature of the high-temperature sintering is 1500°C, and the holding time of the high-temperature sintering is 0.5 hour, to obtain a cemented carbide material.

[0070] Comparative Example 1

[0071] The only difference between this comparative example and Example 1 is that no nanocomposite powder is added.

[0072] Calculated by mass percentage, the raw materials of the cemented carbide material are: 77% WC powder, 10% TiB2 powder, 7% Co powder, 4% Ni powder, 0.8% Mo powder and 1.2% Cr3C2 powder.

[0073] Comparative Example 2

[0074] The difference between this comparative example and Example 1 is that in the preparation process of the nanocomposite powder, neodymium nitrate hexahydrate is not added in step (2), and the dosage ratio of aluminum nitrate nonahydrate, yttrium nitrate hexahydrate, sodium alginate and ethanol solution is 1:2:0.15:45 mL.

[0075] Comparative Example 3

[0076] The difference between this comparative example and Example 1 is that in the preparation process of the nanocomposite powder, yttrium nitrate hexahydrate is not added in step (2), and the dosage ratio of aluminum nitrate nonahydrate, neodymium nitrate hexahydrate, sodium alginate and ethanol solution is 1:2:0.15:45 mL.

[0077] Comparative Example 4

[0078] The difference between this comparative example and Example 1 is that in the preparation process of the nanocomposite powder, the graphene is replaced by aluminum nitride nanotubes in step (2).

[0079] Comparative Example 5

[0080] The only difference between this comparative example and Example 1 is that no TiB2 powder is added.

[0081] Calculated by mass percentage, the raw materials of the cemented carbide material are: 73% WC powder, 7% Co powder, 4% Ni powder, 10.8% Mo powder, 1.2% Cr3C2 powder and 4% nano composite powder.

[0082] Comparative Example 6

[0083] The only difference between this comparative example and Example 1 is that no Mo powder is added.

[0084] Calculated by mass percentage, the raw materials of the cemented carbide material are: 73% WC powder, 10.8% TiB2 powder, 7% Co powder, 4% Ni powder, 1.2% Cr3C2 powder and 4% nano composite powder.

[0085] Comparative Example 7

[0086] The difference between this comparative example and Example 1 is only that the ratio of raw materials is different.

[0087] Calculated by mass percentage, the raw materials of the cemented carbide material are: 50% WC powder, 20% TiB2 powder, 10% Co powder, 10% Ni powder, 1.0% Mo powder, 2.0% Cr3C2 powder and 7.0% nano composite powder.

[0088] Effect test

[0089] The products of Examples 1-3 and Comparative Examples 1-7 were subjected to transverse rupture strength test (GB / T 3851-2015), fracture toughness test (indentation method), Vickers hardness test (GB / T 4340.1-2009), wear resistance test (friction and wear test was carried out by ball-disc method, with a loading force of 100N, a rotation speed of 100r / min, a time of 45min, and the wear amount was recorded) and oxidation resistance test (oxidation at 900°C for 1h, and the unit surface weight gain of cemented carbide was tested). The results are shown in Table 1.

[0090] Table 1 Test results According to Table 1, the cemented carbide materials of Examples 1-3 have better transverse fracture strength, fracture toughness and lower wear. Comparative Examples 1-4 show that specific nanocomposite powders can improve the hardness, wear resistance and fracture toughness of the material. Yttrium nitrate hexahydrate and neodymium nitrate hexahydrate are added during the preparation process, and the two have a synergistic effect; Comparative Examples 5-6 show that TiB2 powder and Mo powder can improve the hardness of cemented carbide to a certain extent, and can significantly improve the fracture toughness and high temperature oxidation resistance of cemented carbide. The present invention significantly improves hardness, fracture toughness, etc. through specific raw material composition and ratio, thereby improving the service life of cemented carbide in harsh environments.

[0091] The above detailed description is a specific description of one feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the scope of the technical solution of the present invention.

Claims

1. A cemented carbide material, characterized in that: Calculated by mass percentage, the raw materials of the cemented carbide material include: 70%-80% WC powder, 5%-15% TiB2 powder, 6%-9% Co powder, 2%-8% Ni powder, 0.4%-1.0% Mo powder, 0.6%-1.6% Cr3C2 powder and 3%-5% nano composite powder.

2. The cemented carbide material according to claim 1, characterized in that: The preparation method of the nanocomposite powder comprises the following steps: (1) mixing graphene and anhydrous ethanol, and dispersing them by ultrasonication to obtain a mixture 1; (2) mixing aluminum nitrate nonahydrate, yttrium nitrate hexahydrate, neodymium nitrate hexahydrate, sodium alginate and ethanol solution, adding the mixture to mixture 1, and sonicating to obtain mixture 2; (3) heating the mixture 2, adjusting the pH, cooling and standing, centrifuging, washing, and drying to obtain a precursor powder; (4) calcining the precursor powder to obtain nanocomposite powder.

3. The cemented carbide material according to claim 2, characterized in that: The mass volume ratio of the graphene to anhydrous ethanol in step (1) is 10 mg: 15-25 mL; the mass ratio of the aluminum nitrate nonahydrate, yttrium nitrate hexahydrate, neodymium nitrate hexahydrate and sodium alginate in step (2) is 1: 0.8-1.2: 0.8-1.2: 0.1-0.2, the mass volume ratio of the aluminum nitrate nonahydrate to the ethanol solution is 1 g: 40-50 mL, and the mass concentration of the ethanol solution is 65%-75%.

4. The cemented carbide material according to claim 2, characterized in that: The mass ratio of the graphene in step (1) to the aluminum nitrate nonahydrate in step (2) is 1:45-55. In step (3), the mixture is heated to 75-80° C., the pH value is adjusted to 7.5-8, the solution used for adjusting the pH value is an ammonia solution, and the mixture is allowed to stand for 22-26 hours. The drying is vacuum drying.

5. The cemented carbide material according to claim 2, characterized in that: The calcination procedure in step (4) is: heating to 1100-1150° C. at 3-5° C. / min and keeping the temperature for 60-80 min.

6. The cemented carbide material according to claim 1, characterized in that: Calculated by mass percentage, the WC powder includes: 40%-60% of WC powder with a particle size of 0.6-0.8 μm and 40%-60% of WC powder with a particle size of 0.8-1.1 μm.

7. A method for preparing the cemented carbide material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Under nitrogen protection, the raw material of the cemented carbide material, the wet grinding medium and the forming agent are mixed and wet-grinded to obtain a slurry; S2, vacuum drying the slurry, sieving, and obtaining alloy powder; S3, pressing the alloy powder into a shape and performing vacuum sintering to obtain a cemented carbide material.

8. The preparation method according to claim 7, characterized in that: In step S1, the wet grinding medium is anhydrous ethanol, the mass ratio of the wet grinding medium to the raw material of the cemented carbide material is 1:0.5-1, the molding agent is paraffin, and the addition amount of the paraffin is 2%-5% of the raw material of the cemented carbide material.

9. The preparation method according to claim 7, characterized in that: In step S2, the steel is sieved with a mesh of 100-200. In step S3, the sintering includes low-temperature sintering, medium-temperature sintering and high-temperature sintering performed in sequence. The temperature of the low-temperature sintering is 440-480°C, and the insulation time of the low-temperature sintering is 1-2h. The temperature of the medium-temperature sintering is 900-950°C, and the insulation time of the medium-temperature sintering is 1-2h. The temperature of the high-temperature sintering is 1200-1500°C, and the insulation time of the high-temperature sintering is 0.5-2h.

10. Use of the cemented carbide material according to any one of claims 1 to 6 or the cemented carbide material prepared by the preparation method according to any one of claims 7 to 9 in preparing kitchen knives.

Citation Information

Patent Citations

  • Hard alloy material for tool

    CN108914018A